Pendidikan Inklusi dalam Legenda Asal Mula Tanaman Padi di Sumba - Kelen, Konradus Doni; Kami, Kanisius; Bitu, Yuliana Sesi; Zaingo, Petronela (Universitas Muhammadiyah Magelang, 2026)
Inclusive education in today's society is increasingly gaining ground, as awareness of equal rights and obligations grows. Gender equity has become a particularly compelling theme. Sumba Island, known for its strong patriarchal cultural practices, possesses a wealth of local wisdom that deeply protects and honors women as individuals worthy of respect. The legend of the origin of the rice plant is one example of local wisdom that deeply appreciates women's integrity in building a shared life. The purpose of this study is to build awareness of inclusion in Sumba, where women's presence is often overlooked in daily cultural practices and often treated unfairly. This study used a qualitative method with an ethnographic approach. Data were collected through in-depth interviews with informants consisting of community leaders and traditional elders. Data were analyzed descriptively and qualitatively. The results of this study indicate that, from the legend of the Origin of the Rice Plant, the Sumbanese actually highly value and give a special place to women. This means that from the beginning, women in Sumbanese culture have been highly respected. Any recent practice of injustice against women is a violation of that culture itself.